Role of NLRP3 in the pathogenesis and treatment of gout arthritis - Liu, Ya-ru; Wang, Jie-quan; Li, Jun (Frontiers in Immunology, 2023)
Gout arthritis (GA) is a common and curable type of inflammatory arthritis that has been attributed to a combination of genetic, environmental and metabolic factors. Chronic deposition of monosodium urate (MSU) crystals in articular and periarticular spaces as well as subsequent activation of innate immune system in the condition of persistent hyperuricemia are the core mechanisms of GA. As is well known, drugs for GA therapy primarily consists of rapidly acting anti-inflammatory agents and life-long uric acid lowering agents, and their therapeutic outcomes are far from satisfactory. Although MSU crystals in articular cartilage detected by arthrosonography or in synovial fluid found by polarization microscopy are conclusive proofs for GA, the exact molecular mechanism of NLRP3 inflammasome activation in the course of GA still remains mysterious, severely restricting the early diagnosis and therapy of GA. On the one hand, the activation of Nod-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome requires nuclear factor kappa B (NF-κB)-dependent transcriptional enhancement of NLRP3, precursor (pro)-caspase-1 and pro-IL-1β, as well as the assembly of NLRP3 inflammasome complex and sustained release of inflammatory mediators and cytokines such as IL-1β, IL-18 and caspase-1. On the other hand, NLRP3 inflammasome activated by MSU crystals is particularly relevant to the initiation and progression of GA, and thus may represent a prospective diagnostic biomarker and therapeutic target. As a result, pharmacological inhibition of the assembly and activation of NLRP3 inflammasome may also be a promising avenue for GA therapy. Herein, we first introduced the functional role of NLRP3 inflammasome activation and relevant biological mechanisms in GA based on currently available evidence. Then, we systematically reviewed therapeutic strategies for targeting NLRP3 by potentially effective agents such as natural products, novel compounds and noncoding RNAs (ncRNAs) in the treatment of MSU-induced GA mouse models. In conclusion, our present review may have significant implications for the pathogenesis, diagnosis and therapy of GA.